The Revival of American Hegemony - Maria da Conceigäo Tavares (CEPAL Review, 1985)
One of the most striking features of international economic and political relations in recent years has been the revival of United States power in the Western world. After a couple of decades in which a situation of multipolarity seemed to be consolidating itself in the structure of the relations among the developed capitalist countries, there is once again a concentration of power in the hands of the country which, of course, has been for many years now the main centre of the world economy.